Evaluation of the CHADS2 Risk Score on Short‐ and Long‐Term All‐Cause and Cardiovascular Mortality After Syncope. Issue 5 (28th February 2013) - Ruwald, Martin Huth; Ruwald, Anne‐Christine; Jons, Christian; Lamberts, Morten; Hansen, Morten Lock; Vinther, Michael; Køber, Lars; Torp‐Pedersen, Christian; Hansen, Jim; Gislason, Gunnar Hilmar
Abstract Background Syncope risk stratification is difficult and has not been implemented clinically. Hypothesis The CHADS2 score can be applied as a risk stratification tool for predicting mortality after an episode of syncope. Methods All patients discharged from emergency departments with a first‐time diagnosis of syncope from 2001 to 2009 where identified from nationwide registers in Denmark and matched on sex and age with a control population. Risk of all‐cause or cardiovascular death was analyzed by multivariable Cox models. Results A total of 37 705 patients were included. There were a total of 7761 deaths (21%), of which 52% were cardiovascular vs 27 862 (15%) deaths in the control population. The risk of cardiovascular death was significantly increased with increasing CHADS2 score (CHADS2 score: 1–2, hazard ratio [HR]: 9.11, 95% confidence interval [CI]: 8.25‐10.07; CHADS2 score: 3–4, HR: 17.32, 95% CI: 15.42‐19.47; CHADS2 score: 5–6, HR: 26.66, 95% CI: 21.40‐33.21) relative to CHADS2 score of 0. A CHADS2 score of 0 was associated overall with very low event rates (15.1 deaths per 1000 person‐years) but was associated with increased relative risk in the syncope population compared to controls. Syncope predicted 1‐week, 1‐year, and long‐term mortality across CHADS2 scores compared to controls but did not reach significance in CHADS2 scores of 5 to 6. Conclusions Increasing CHADS2 score significantly predicts mortality in patients discharged with a diagnosis of syncope, and a CHADS2 score of 0 was associated with a very low absolute mortality. Compared to controls, syncope was associated with increased short‐ and long‐term mortality, particularly in the lower CHADS2 scores.